(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
The article focuses on the herbarium analysis of the toponymy of that time on the example of the work "Boburnoma". Toponymic materials are supported by examples from historical works. In the process of comparative analysis, the distributive and artistic possibilities of toponyms are shown. The ability of the poet to use linguopoetic tools in the ruby is drawn into the analysis of herbarism. The ability of the word to create and form concepts is given with examples. The possibilities of poetic language to create art and the criteria of socio-political factor in this regard are analyzed.